DRIVING ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN HIGHER EDUCATION: THE ROLE OF SUPERVISORY SUPPORT, PERCEIVED ORGANIZATIONAL SUPPORT AND RELIGIOSITY - Euis Nessia Fitri; Soewarto Hardhienata; Griet Helena Laihad (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyse the influence of supervisory support and perceived organisational support (POS) on organisational citizenship behaviour (OCB), considering religiosity as a mediating variable among private vocational school teachers in Greater Tangerang. This study is important because teachers' organisational citizenship behaviour plays a role in improving school effectiveness, but the mechanisms of its formation in value-based professions such as teaching are not yet fully understood. The research uses a quantitative approach with an explanatory design. Data were collected from 217 teachers selected through proportionate stratified random sampling from a population of 476 private vocational school teachers. Data analysis was performed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 through evaluation of the measurement model and structural model, including validity, reliability, coefficient of determination (R²), effect size (f²), predictive relevance (Q²), and mediation tests using bootstrapping. The results showed that supervisory support had a positive and significant effect on teacher religiosity, indicating that supportive leadership could strengthen spiritual values in the work environment. However, SS and POS did not have a significant effect on OCB, and the religiosity variable was not proven to significantly affect OCB. Furthermore, religiosity did not mediate the relationship between organisational support and OCB. These findings indicate that